Do we care about sustainability? An analysis of time sensitivity of social preferences under environmental time-persistent effects. (15th July 2016) - Faccioli, Michela; Hanley, Nick; Torres, Cati; Font, Antoni Riera
Abstract: Environmental cost-benefit analysis has traditionally assumed that the value of benefits is sensitive to their timing and that outcomes are valued higher, the sooner in time they occur following implementation of a project or policy. Though, this assumption might have important implications especially for the social desirability of interventions aiming at counteracting time-persistent environmental problems, whose impacts occur in the long- and very long-term, respectively involving the present and future generations. This study analyzes the time sensitivity of social preferences for preservation policies of adaptation to climate change stresses. Results show that stated preferences are time insensitive, due to sustainability issues: individuals show insignificant differences in benefits they can experience within their own lifetimes compared to those which occur in the longer term, and which will instead be enjoyed by future generations. Whilst these results may be specific to the experimental design employed here, they do raise interesting questions regarding choices over time-persistent environmental problems, particularly in terms of the desirability of interventions which produce longer-term benefits. Highlights: We study the role of sustainability concerns in social preferences in the face of environmental time-persistent problems. The analysis relies on a choice experiment to compare preferences for nature preservation over the long- and very long-run. It shows that preferences are time-insensitive due to sustainability issues. Willingness to pay does not depend on whether present or future generations will benefit from the preservation policy.